PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF DAN TEKNIK MENGAJUKAN PERTANYAAN EDARKAN TOPI TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA SMPN 23 PADANG - Safatma, Yeni; Rismen, Sefna; Lovia, Lita (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was motivated by the students understanding on mathematics concept that still low thus causing students mathematics learning outcomes also becomes low. This research was aimed at revealing whether the use of cooperative learning and asking questions circulate hat techniques better effect on the studentsâ understanding on mathematics concept than the conventional one in class VIII of SMPN 23 Padang. This was an experimental research which used random research design toward the subject. Population in this research is all class student of VIII SMPN 23 Padang. Technique intake of sampel conductedat random, choosen as class of sampel is VIII1 as experiment class and of VIII3 as control class. The instrument used in this research is a test in studentsâ understanding on mathematics concept with a reliability test r11 = 0.88 . The data Â was analyzed by using t-test. . Based on the result of data analysis known that thitung = 5,37 and ttabel = 1,669 with Î± = 0.05. So thitung > ttabel it can be concluded that the applicationÂ of students understanding of mathematical concepts by implementing cooperative learning and asking questions circulate hat techniques are better effect on the studentsâ understanding on mathematics concept than a conventional one .Â